Question
upstudy study bank question image url

for \( u \) \( 2(u+9)=-5 u-3 \) lify your answer as

Ask by Christensen Wright. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( u = -3 \)

Solution

Solve the equation \( 2(u+9)=-5u-3 \). Solve the equation by following steps: - step0: Solve for \(u\): \(2\left(u+9\right)=-5u-3\) - step1: Expand the expression: \(2u+18=-5u-3\) - step2: Move the expression to the left side: \(2u+5u=-3-18\) - step3: Add and subtract: \(7u=-3-18\) - step4: Add and subtract: \(7u=-21\) - step5: Divide both sides: \(\frac{7u}{7}=\frac{-21}{7}\) - step6: Divide the numbers: \(u=-3\) The solution to the equation \(2(u+9)=-5u-3\) is \(u=-3\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

First, let’s simplify the equation step by step! Start by distributing the \(2\) to both terms in the parentheses: \(2u + 18 = -5u - 3\). Now, let's get all the \(u\) terms on one side and constant terms on the other. Add \(5u\) and subtract \(18\) from both sides, leading you to \(7u = -21\). Divide both sides by \(7\) to find \(u = -3\). Now, this little gem, \( u = -3 \), is the solution to our equation! Don't forget to check by plugging it back into the original equation to ensure both sides are equal—it's like a hidden treasure hunt!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy